2013
DOI: 10.1055/s-0033-1350084
|View full text |Cite
|
Sign up to set email alerts
|

Technique: Osteochondral Grafting of Capitate Chondrosis in PRC

Abstract: Proximal row carpectomy (PRC) has been shown in multiple studies to be an effective motion-preserving procedure for wrist arthritis. The operation consists of resection of the scaphoid, lunate, and triquetrum. 1 The proximal capitate and lunate fossa of the radius form the new wrist articulation, which makes the ideal patient free of degenerative changes at those articular surfaces. 2-8 Various authors, as well as the senior author, have maintained that when there is mild degeneration of these articular surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Notably, in a series of 17 patients, it was found that six required conversion to radiocarpal arthrodesis at an average of 11 yr. 4 Technical variations to PRC, such as interposition of tissues into the radio-capitate joint and resurfacing of the capitate have been considered in order to delay conversion. [10][11][12][13][14][15][16][17][18][19] These variations have allowed indications for PRC to expand to new patient populations, such as those with degeneration of the capitate head, Kienbock's disease, and complex carpal fractures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, in a series of 17 patients, it was found that six required conversion to radiocarpal arthrodesis at an average of 11 yr. 4 Technical variations to PRC, such as interposition of tissues into the radio-capitate joint and resurfacing of the capitate have been considered in order to delay conversion. [10][11][12][13][14][15][16][17][18][19] These variations have allowed indications for PRC to expand to new patient populations, such as those with degeneration of the capitate head, Kienbock's disease, and complex carpal fractures.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13]20,21 Resurfacing techniques using osteochondral grafts or pyrocarbon implants to create a new proximal surface for the capitate have also been described. [14][15][16][17][18][19] Although both interposition and resurfacing have demonstrated similar outcomes to standard PRC, it remains unknown which variation should be considered superior in terms of outcomes and survivability. 10,11,18 Therefore, studies evaluating patients receiving either treatment continue to be essential to inform treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation